Characterization of hydrochar from hydrothermal carbonization of maize residues - Nakorn Tippayawong; Piyacha Kantakanit; Sirichai Koonaphapdeelert (Energy Reports, 2020)
Utilization of agro-residues from maize production as biorenewable energy source is considered to be a very good and sustainable waste management method. Hydrothermal carbonization (HTC) is a thermochemical conversion process for solid organic materials at elevated temperature and pressure in the presence of water. Through hydrolysis, dehydration and decarboxylation, a solid hydrochar as well as gaseous and aqueous products are generated. The energy density and the macromolecular structure of the solid product are improved, giving rise to a carbonized product that is simpler to convert to heat, power or fuel than the starting materials. This study was about applying HTC to upgrade maize residues. The residues used were cobs derived from a maize processing factory. The HTC experiments were carried out in a batch 10-dm3 pressure reactor equipped with 14 kW heaters and internal temperature control. About 0.5~kg of biomass was loaded with 5 dm3 of deionized water into the reactor. The effects of temperature (180-250~°C) and time (60-360 min) were examined. The hydrochar was recovered by filtration and dried for subsequent analyses. With increasing temperature and time, the amount of hydrochar was found to decrease, while the gaseous and aqueous products increased. Hydrochar yields were in the range of about 35%-72%. From the analysis result, hydrochar produced was found to have improved fuel qualities Its elemental composition was coalified with H/C and O/C atomic ratios moving towards that of lignite.
Keywords: 330; Agricultural waste; Biomass conversion; Hot compressed water; Renewable energy; Wet pyrolysis